2020
DOI: 10.1002/mma.6178
|View full text |Cite
|
Sign up to set email alerts
|

Fractional KdV and Boussenisq‐Burger's equations, reduction to PDE and stability approaches

Abstract: The generalized fractional Caputo‐operator is discussed. The reduction of partial differential equations retarded or advanced with delays is obtained. The applications to the space‐time‐fractional KdV and time‐fractional Boussenisq‐Burger's equation are carried. Semi‐self‐similar SS wave solutions are obtained. That is, there exists a soliton wave propagates along a specific characteristic curve in the xt‐ plane. This may be due to the effects associated with the distributed time delay. The effects of space f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The unified, extended and generalized unified methods have been proposed in [42][43][44][45][46][47][48][49]. The unified method asserts that , the solutions of a nonlinear evolution equation can be written in the forms of polynomial or rational functions in auxiliary functions, that satisfy appropriate auxiliary equations.…”
Section: Solutions Of the Fractal And Fractional Time-derivative Bnementioning
confidence: 99%
“…The unified, extended and generalized unified methods have been proposed in [42][43][44][45][46][47][48][49]. The unified method asserts that , the solutions of a nonlinear evolution equation can be written in the forms of polynomial or rational functions in auxiliary functions, that satisfy appropriate auxiliary equations.…”
Section: Solutions Of the Fractal And Fractional Time-derivative Bnementioning
confidence: 99%
“…Here, we shall reduce the fractional derivatives to non autonomous ordinary derivatives, that is with time dependent coefficients [22][23][24].…”
Section: Reduction Of the Fractional Derivativesmentioning
confidence: 99%
“…By inserting (22) and ( 23) into (21), and by using (24), we get a system of nonlinear algebraic equations in a i (v), b i (v) and d i (v), i = 1, 2... . We found that the calculations are not straight forward due to two facts.…”
Section: Case Of Linear Auxiliary Equationsmentioning
confidence: 99%
“…Osman et al, 43 obtained double‐wave solutions of coupled Burgers' equation by employing the generalized unified method (GUM). Abdel‐Gawad et al, 44 investigated both of fractional KdV and Boussenisq–Burger's equations by using the unified method to attain semi‐self‐similar wave solutions. Sweilam et al, 45 presented a numerical technique to investigate complex order of fractional nonlinear Burgers' equation.…”
Section: Introductionmentioning
confidence: 99%